Innovating Murabahah through Hybrid Contracts: A Normative Juridical Analysis of Sharia-Compliant Financial Practices and Governance in Islamic Banking - Siregar, Muhammad Islah; Ikhsan, Muhammad Miftahul; Abdurrahman, Nana Herdiana; Setiawan, Iwan; Fadillah, M Rizki (CV. Strata Persada Academia, 2025)
This study investigates the application of the hybrid contract concept in murabahah financing within Islamic banking, focusing on its legal validity, operational procedures, and compliance with Sharia principles. Hybrid contracts (al-‘uqud al-murakkabah), which integrate multiple contractual elements into a unified framework, have emerged as a significant innovation to address the limitations of conventional murabahah structures in meeting complex financing demands. Employing a normative juridical research design with a qualitative-descriptive approach, this research analyzes primary Islamic legal sources (Qur’an, Hadith, and classical fiqh), relevant regulations, and fatwas, particularly DSN-MUI Fatwa No. 04/DSN-MUI/IV/2000, alongside secondary literature on Islamic finance. The findings reveal that the hybrid contract model, particularly al-murabahah wa ar-rahn (murabahah with collateral), is legally permissible and aligns with the maqasid al-shariah when implemented with full asset ownership and risk assumption by the bank prior to contract execution. The study contributes to the discourse on Sharia-compliant financial innovation by proposing standardized governance protocols, enhanced transparency, and adaptive legal frameworks to strengthen hybrid murabahah financing practices.